Manganese-silicon-aluminum-chromium series high-strength steel suitable for additive manufacturing
By adjusting the composition and process parameters of manganese-silicon-aluminum-chromium high-strength steel in additive manufacturing, the problems of poor moldability and high cost of existing high-strength steels are solved, and the additive manufacturing effect with low cost, high strength and good plasticity is achieved.
Patent Information
- Application Number
- CN202311059877.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-02-25
AI Technical Summary
Existing high-strength steels have poor moldability and high cost in the additive manufacturing process, and low-cost low-alloy steels are prone to cracks in additive manufacturing, making it difficult to meet the needs of steel materials between high strength and low cost.
Using laser additive manufacturing technology, the composition and process parameters of manganese-silicon-aluminum-chromium high-strength steel were adjusted and optimized, and a high-strength steel with low-cost alloy content was prepared. The chemical composition was C: 0.20-0.65%, Mn: 3.0-6.5%, Cr: 0.6-1.4%, Si: 0.6-2.8%, Al: 0.6-1.5%, and the balance was Fe.
It has achieved good moldability and high strength of manganese-silicon-aluminum-chromium high-strength steel in additive manufacturing, has good density and plasticity, and has reduced production costs.
Smart Images

Figure CN119506728A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal additive manufacturing, and in particular to a manganese-silicon-aluminum-chromium series high-strength steel suitable for additive manufacturing. Background Art
[0002] Additive manufacturing technology is an advanced manufacturing technology that has emerged in the past 40 years and integrates optics, electromechanics, computers, numerical control and new materials. Additive manufacturing technology has changed the manufacturing method based on cutting materials in traditional processing technology. It directly generates three-dimensional entities by stacking discrete materials such as powder, liquid or sheet, filament, etc. layer by layer. In theory, you only need to design a structural model on the computer, and you can use this technology to bypass the complex production process of traditional manufacturing and quickly turn the designed model into a physical object. This is in line with the development trend of modern and future manufacturing industries for personalized, customized and specialized products. Therefore, additive manufacturing technology has led to revolutionary progress in manufacturing technology.
[0003] At present, the research and production of advanced high-strength steel (AHSS) has always been valued by the steel research community and the business community. With the continuous upgrading of steel products, higher requirements are placed on the strength of steel materials, and high-strength steel has gradually become a research hotspot. High-strength steel is a high-strength steel material developed on the basis of traditional alloy structural steel. The alloying and heat treatment processes can significantly improve its strength while obtaining good toughness. High-strength steel has a wide range of applications, including machinery manufacturing, vehicle engineering, shipbuilding and other fields. In addition, it can also be used in special fields such as armored vehicle steel plates and transport aircraft landing gear. Therefore, high-strength steel has broad application prospects and is an important development and research direction for advanced high-strength steel materials.
[0004] Such as 17-4PH martensitic precipitation hardening high-strength steel and 18Ni300 martensitic aging steel, they have good formability when used in additive manufacturing, but due to the high content of alloy elements, their prices and manufacturing costs also increase accordingly; while the existing mature low-cost steels with low alloy element content used in traditional manufacturing processes, such as 40Cr, 40Mn, 45 steel, etc., are prone to cracks in the process of additive manufacturing, have poor formability, and have a tendency to crack when manufacturing large or complex parts, and the processability needs to be improved. Under the development trend of ultra-high strength of steel materials, it is an important issue in the development of steel materials to consider production costs while ensuring that the steel has good strength and plastic toughness. Therefore, it is urgent to provide a new type of low-cost high-strength steel suitable for additive manufacturing. Summary of the invention
[0005] In order to meet the requirements of high strength and good plasticity and toughness of steel materials, the present invention uses laser additive manufacturing technology to adjust and optimize the high-strength steel composition and additive manufacturing process parameters, and proposes a manganese-silicon-aluminum-chromium high-strength steel with good plasticity and toughness. Experiments show that this steel has good formability and processability.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, whose chemical composition is as follows by mass percentage: C: 0.20-0.65%, Mn: 3.0-6.5%, Cr: 0.6-1.4%, Si: 0.6-2.8%, Al: 0.6-1.5%, and the balance is Fe.
[0008] Preferably, the chemical composition by mass percentage is: C: 0.30-0.45%, Mn: 3.8-5.0%, Cr: 0.8-1.2%, Si: 0.9-1.6%, Al: 0.8-1.2%, and the balance is Fe. Under this composition, the comprehensive performance of the manganese-silicon-aluminum-chromium high-strength steel is more excellent.
[0009] The method for manufacturing manganese-silicon-aluminum-chromium high-strength steel based on laser additive manufacturing specifically includes the following steps:
[0010] (1) preparing high-strength steel powder with a particle size of 15 to 53 μm by vacuum melting, gas atomization, and powder screening in accordance with the designed composition ratio;
[0011] (2) Using the high-strength steel powder obtained in step (1), a high-strength steel block is prepared by laser powder bed melting additive manufacturing technology.
[0012] Preferably, high-strength steel blocks are prepared by laser powder bed melting additive manufacturing technology, and the process parameters are set as follows: a laser with a spot diameter of 130 μm is selected, a scanning strategy of rotating the laser scanning direction by 67° for each layer is adopted, the laser power is set to 180-260 W, the scanning speed is 600-1800 mm / s, the scanning interval is 70 μm, and the powder layer thickness is 30 μm.
[0013] Preferably, the room temperature tensile strength, yield strength and elongation after fracture of the prepared manganese-silicon-aluminum-chromium high-strength steel are 1300-1650 MPa, 1050-1450 MPa and 8.0-24.0%, respectively.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] The present invention designs a low-cost, medium-alloy-content manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing. A large number of experimental results show that the alloy system has good formability when used for laser additive manufacturing, has no obvious pores and unfused holes, has no cracks in the additive block, and has good density. Tensile test results show that the room-temperature tensile strength, yield strength and elongation after fracture of the tensile specimens obtained by additive manufacturing are 1300-1650MPa, 1050-1450MPa, and 8.0-24.0%, respectively. The specimens additively manufactured with the manganese-silicon-aluminum-chromium high-strength steel have good formability, and the additive body has both high strength and good plasticity. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a morphology diagram of the manganese-silicon-aluminum-chromium spherical powder prepared in the present invention.
[0017] Figure 2 This is the SEM image of the microstructure of the block sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0018] The present invention provides a manganese-silicon-aluminum-chromium series high-strength steel suitable for additive manufacturing, wherein the high-strength steel contains alloy elements such as Mn, Cr, Si, and Al. The prepared additive block has good formability, no defects such as cracks and pores, high density, and good strength and plasticity.
[0019] The manganese-silicon-aluminum-chromium high-strength steel alloy suitable for additive manufacturing described in the present invention has the following chemical compositions by mass percentage: C: 0.20-0.65%, Mn: 3.0-6.5%, Cr: 0.6-1.4%, Si: 0.6-2.8%, Al: 0.6-1.5%, and the remainder is Fe.
[0020] The main chemical composition of the steel grade of the present invention is limited for the following reasons:
[0021] Carbon: C is the main additive element in steel, forming solid solution strengthening and improving hardness in steel. As the carbon content increases, the hardenability of the steel increases. A large number of experimental results show that the appropriate carbon content of the manganese-silicon-aluminum-chromium high-strength steel suitable for the present invention is C: 0.25-0.65%.
[0022] Manganese: Mn plays a role of solid solution strengthening in steel, expands the γ phase region, increases the stability of austenite, and improves the mechanical properties of steel. A large number of experimental results show that the appropriate carbon content of the manganese-silicon-aluminum-chromium high-strength steel suitable for the present invention is Mn: 3.0-6.5%.
[0023] Silicon: Si will reduce the γ phase area, inhibit the formation of carbides, can be dissolved in austenite, and has a strong effect on improving the hardenability of the material. It can improve the tempering stability of steel and has a secondary hardening effect, but too high Si content will reduce the plasticity and toughness of the material. A large number of experimental results show that the appropriate silicon content of the manganese-silicon-aluminum-chromium high-strength steel suitable for the present invention is Si: 0.6-2.8%.
[0024] Aluminum: Al can inhibit the precipitation of carbides. A small amount of Al can improve the plasticity and toughness of steel, but too much Al will affect the welding and cutting performance of steel. A large number of experimental results show that the appropriate aluminum content of the manganese-silicon-aluminum-chromium high-strength steel suitable for the present invention is Al: 0.6-1.5%.
[0025] Chromium: Cr will reduce the γ phase area, can be infinitely dissolved in α iron, improve the strength and hardness of steel, and can also improve the oxidation resistance and corrosion resistance of steel. A large number of experimental results show that the appropriate chromium content of the manganese-silicon-aluminum-chromium high-strength steel suitable for the present invention is: 0.6-1.4%.
[0026] The above-mentioned method for preparing the manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing specifically comprises the following steps:
[0027] According to the designed composition ratio, manganese-silicon-aluminum-chromium high-strength steel powder with a particle size of 15 to 53 μm is prepared by vacuum melting, gas atomization, and powder screening, and the powder is prepared into a steel block by laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° for each layer is adopted. The laser power is set to 180 to 280 W, the scanning speed is 600 to 1800 mm / s, the scanning interval is 70 μm, and the powder layer thickness is 30 μm. The block sample of the steel is additively manufactured on the substrate. Due to the differences in the composition of each element in different embodiments, in order to ensure the formability of the steel block manufactured by additive manufacturing, the printing parameters of each embodiment also vary within a certain range.
[0028] The mechanical properties of the finally obtained manganese-silicon-aluminum-chromium high-strength steel are as follows: room temperature tensile strength 1300-1650 MPa, yield strength 1050-1450 MPa, and elongation after fracture 8.0-24.0%.
[0029] Embodiment 1:
[0030] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, whose chemical composition is as follows by mass ratio: C: 0.35%, Mn: 4.7%, Cr: 0.98%, Si: 0.95%, Al: 1.00%, and the balance is Fe.
[0031] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization and powder screening are carried out in sequence to obtain alloy powders with a size of 15 to 53 μm (the powder morphology is as follows Figure 1 As shown), the powder of the component was made into a steel block using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130μm was selected, and a scanning strategy of rotating the laser scanning direction by 67° for each layer was adopted. The laser power was set to 180W, the scanning speed was 600mm / s, the scanning spacing was 70μm, and the powder layer thickness was 30μm. The block sample with a size of 10×10×10cm was obtained by additive manufacturing. The prepared samples were cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0032] Observe the microstructure of the bulk sample (such as Figure 2 The matrix structure is lath martensite (M) and austenite (A); the sample has no obvious defects such as pores, unfused holes, cracks, etc., and has good density.
[0033] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break in the direction parallel to the substrate were 1608MPa, 1346MPa and 24.0%, respectively; the room temperature tensile strength, yield strength and elongation at break in the direction perpendicular to the substrate were 1586MPa, 1326MPa and 22.0%, respectively.
[0034] Embodiment 2:
[0035] A manganese-silicon-aluminum-chromium series high-strength steel suitable for additive manufacturing, wherein the chemical composition thereof is calculated by mass ratio as follows: C: 0.20%, Mn: 3.0%, Cr: 0.60%, Si: 0.60%, Al: 0.60%, and the balance is Fe.
[0036] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization, and powder screening are carried out in sequence to obtain alloy powders of 15 to 53 μm, and the powder components are made into steel blocks using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer is adopted. The laser power is set to 200 W, the scanning speed is 600 mm / s, the scanning spacing is 70 μm, and the powder layer thickness is 30 μm. The block sample with a size of 10×10×10 cm is obtained by additive manufacturing. The prepared samples are cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0037] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as pores, unfused holes, cracks, etc. and had good density.
[0038] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break in the direction parallel to the substrate were 1450MPa, 1164MPa and 14.8%, respectively; the room temperature tensile strength, yield strength and elongation at break in the direction perpendicular to the substrate were 1423MPa, 1185MPa and 13.0%, respectively.
[0039] Embodiment 3:
[0040] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, whose chemical composition is as follows by mass ratio: C: 0.31%, Mn: 3.8%, Cr: 0.80%, Si: 0.95%, Al: 0.80%, and the balance is Fe.
[0041] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization, and powder screening are carried out in sequence to obtain alloy powders of 15 to 53 μm, and the powder components are made into steel blocks using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer is adopted. The laser power is set to 220 W, the scanning speed is 600 mm / s, the scanning spacing is 70 μm, and the powder layer thickness is 30 μm. The block sample with a size of 10×10×10 cm is obtained by additive manufacturing. The prepared samples are cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0042] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as pores, unfused holes, cracks, etc. and had good density.
[0043] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break parallel to the substrate were 1530MPa, 1208MPa and 15.0%, respectively; the room temperature tensile strength, yield strength and elongation at break perpendicular to the substrate were 1510MPa, 1186MPa and 14.6%, respectively.
[0044] Embodiment 4:
[0045] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, whose chemical composition is as follows by mass ratio: C: 0.36%, Mn: 4.0%, Cr: 1.18%, Si: 1.16%, Al: 1.12%, and the balance is Fe.
[0046] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization, and powder screening are carried out in sequence to obtain alloy powders of 15 to 53 μm, and the powder components are made into steel blocks using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer is adopted. The laser power is set to 240 W, the scanning speed is 900 mm / s, the scanning spacing is 70 μm, and the powder layer thickness is 30 μm. The block sample with a size of 10×10×10 cm is obtained by additive manufacturing. The prepared samples are cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0047] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as pores, unfused holes, cracks, etc. and had good density.
[0048] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break in the direction parallel to the substrate were 1498MPa, 1226MPa and 14.5%, respectively; the room temperature tensile strength, yield strength and elongation at break in the direction perpendicular to the substrate were 1532MPa, 1220MPa and 14.2%, respectively.
[0049] Embodiment 5:
[0050] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, whose chemical composition is as follows by mass ratio: C: 0.40%, Mn: 4.5%, Cr: 1.07%, Si: 1.30%, Al: 1.02%, and the balance is Fe.
[0051] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization, and powder screening are carried out in sequence to obtain alloy powders of 15 to 53 μm, and the powder components are made into steel blocks using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer is adopted. The laser power is set to 240 W, the scanning speed is 1200 mm / s, the scanning spacing is 70 μm, and the powder layer thickness is 30 μm. The block sample with a size of 10×10×10 cm is obtained by additive manufacturing. The prepared samples are cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0052] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as pores, unfused holes, cracks, etc. and had good density.
[0053] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break parallel to the substrate were 1525MPa, 1121MPa and 15.0%, respectively; the room temperature tensile strength, yield strength and elongation at break perpendicular to the substrate were 1495MPa, 1098MPa and 15.8%, respectively.
[0054] Embodiment 6:
[0055] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, wherein the chemical composition thereof is, by mass ratio, C: 0.45%, Mn: 5.0%, Cr: 1.20%, Si: 1.60%, Al: 1.20%, and the balance is Fe.
[0056] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization, and powder screening are carried out in sequence to obtain alloy powders of 15 to 53 μm, and the powder components are made into steel blocks using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer is adopted. The laser power is set to 240 W, the scanning speed is 1500 mm / s, the scanning spacing is 70 μm, and the powder layer thickness is 30 μm. The block sample with a size of 10×10×10 cm is obtained by additive manufacturing. The prepared samples are cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0057] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as pores, unfused holes, cracks, etc. and had good density.
[0058] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break parallel to the substrate were 1610MPa, 1256MPa and 18.0%, respectively; the room temperature tensile strength, yield strength and elongation at break perpendicular to the substrate were 1601MPa, 1276MPa and 15.6%, respectively.
[0059] Embodiment 7:
[0060] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, whose chemical composition is as follows by mass ratio: C: 0.48%, Mn: 5.2%, Cr: 1.38%, Si: 2.05%, Al: 1.21%, and the balance is Fe.
[0061] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization, and powder screening are carried out in sequence to obtain alloy powders of 15 to 53 μm, and the powder components are made into steel blocks using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer is adopted. The laser power is set to 260 W, the scanning speed is 1200 mm / s, the scanning spacing is 70 μm, and the powder layer thickness is 30 μm. The block sample with a size of 10×10×10 cm is obtained by additive manufacturing. The prepared samples are cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0062] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as pores, unfused holes, cracks, etc. and had good density.
[0063] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break in the direction parallel to the substrate were 1578MPa, 1223MPa and 13.2%, respectively; the room temperature tensile strength, yield strength and elongation at break in the direction perpendicular to the substrate were 1562MPa, 1186MPa and 14.5%, respectively.
[0064] Embodiment 8:
[0065] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, whose chemical composition is as follows by mass ratio: C: 0.28%, Mn: 5.5%, Cr: 1.08%, Si: 1.88%, Al: 1.05%, and the balance is Fe.
[0066] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization, and powder screening are carried out in sequence to obtain alloy powders of 15 to 53 μm, and the powder components are made into steel blocks using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer is adopted. The laser power is set to 260 W, the scanning speed is 1500 mm / s, the scanning spacing is 70 μm, and the powder layer thickness is 30 μm. The block sample with a size of 10×10×10 cm is obtained by additive manufacturing. The prepared samples are cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0067] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as pores, unfused holes, cracks, etc. and had good density.
[0068] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break parallel to the substrate were 1545MPa, 1173MPa and 14.6%, respectively; the room temperature tensile strength, yield strength and elongation at break perpendicular to the substrate were 1534MPa, 1132MPa and 13.8%, respectively.
[0069] Embodiment 9:
[0070] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, whose chemical composition is as follows by mass ratio: C: 0.42%, Mn: 6.5%, Cr: 1.02%, Si: 2.25%, Al: 1.01%, and the balance is Fe.
[0071] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization, and powder screening are carried out in sequence to obtain alloy powders of 15 to 53 μm, and the powder components are made into steel blocks using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer is adopted. The laser power is set to 260 W, the scanning speed is 1800 mm / s, the scanning spacing is 70 μm, and the powder layer thickness is 30 μm. The block sample with a size of 10×10×10 cm is obtained by additive manufacturing. The prepared samples are cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0072] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as pores, unfused holes, cracks, etc. and had good density.
[0073] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break in the direction parallel to the substrate were 1640MPa, 1378MPa and 10.5%, respectively; the room temperature tensile strength, yield strength and elongation at break in the direction perpendicular to the substrate were 1637MPa, 1440MPa and 10.0%, respectively.
[0074] Embodiment 10:
[0075] A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, whose chemical composition is as follows by mass ratio: C: 0.65%, Mn: 5.8%, Cr: 1.40%, Si: 2.80%, Al: 1.50%, and the balance is Fe.
[0076] According to the above-mentioned mass ratio of ingredients, vacuum melting, gas atomization, and powder screening are carried out in sequence to obtain alloy powders of 15 to 53 μm, and the powder components are made into steel blocks using laser powder bed melting additive manufacturing technology. A laser with a spot diameter of 130 μm is selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer is adopted. The laser power is 240w, the scanning speed is 1800mm / s, and the scanning spacing is 70μm. The block sample with a size of 10×10×10cm is obtained by additive manufacturing. The prepared samples are cut into two types of samples parallel to the substrate and perpendicular to the substrate.
[0077] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as pores, unfused holes, cracks, etc. and had good density.
[0078] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break in the direction parallel to the substrate were 1634MPa, 1437MPa and 12.5%, respectively; the room temperature tensile strength, yield strength and elongation at break in the direction perpendicular to the substrate were 1645MPa, 1426MPa and 11.5%, respectively.
[0079] Comparative Example 1:
[0080] A commercially available quenched and tempered steel alloy has the following chemical compositions by mass ratio: C: 0.31%, Mn: 0.95%, Cr: 0.92%, Si: 1.05%, and the balance is Fe.
[0081] The alloy powder was made into steel blocks using laser powder bed fusion additive manufacturing technology. A laser with a spot diameter of 130μm was selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer was adopted. The laser power was 240w, the scanning speed was 1200mm / s, and the scanning spacing was 70μm. The block sample with a size of 10×10×10cm was obtained by additive manufacturing. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.
[0082] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as unfused holes, but there was a tendency to crack when preparing larger blocks and complex parts.
[0083] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break in the direction parallel to the substrate were 1234 MPa, 976 MPa and 3.0%, respectively; the room temperature tensile strength, yield strength and elongation at break in the direction perpendicular to the substrate were 1210 MPa, 957 MPa and 2.0%, respectively.
[0084] Comparative Example 2:
[0085] A commercially available quenched and tempered steel alloy has the following chemical compositions by mass ratio: C: 0.82%, Mn: 1.81%, Cr: 1.05%, Si: 0.91%, and the balance Fe.
[0086] The alloy powder was made into steel blocks using laser powder bed fusion additive manufacturing technology. A laser with a spot diameter of 130μm was selected, and a scanning strategy of rotating the laser scanning direction by 67° per layer was adopted. The laser power was 240w, the scanning speed was 1200mm / s, and the scanning spacing was 70μm. The block sample with a size of 10×10×10cm was obtained by additive manufacturing. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.
[0087] Metallographic specimens were made to observe the microstructure of the specimens. The matrix structure was martensite and austenite. The specimens had no obvious defects such as unfused holes, but there was a tendency to crack when preparing larger blocks and complex parts.
[0088] In accordance with the national standard for tensile tests, the additive body was made into tensile test samples that meet the national standards and tensile performance tests were carried out. The room temperature tensile strength, yield strength and elongation at break parallel to the substrate were 1334 MPa, 1026 MPa and 7.5%, respectively; the room temperature tensile strength, yield strength and elongation at break perpendicular to the substrate were 1350 MPa, 1017 MPa and 6.8%, respectively.
[0089] Table 1 and Table 2 respectively give the ingredients and test results of each embodiment and comparative example.
[0090] Table 1 Composition of each embodiment and comparative example (wt.%)
[0091]
[0092]
[0093] Note: The balance is Fe.
[0094] Table 2 Actual measured values of various performances
[0095]
[0096] Note: lateral σ b , σ 0.2 , δ are the tensile strength, yield strength and elongation parallel to the substrate direction, and the longitudinal σ b , σ 0.2 , δ are the tensile strength, yield strength and elongation at break perpendicular to the substrate.
[0097] The high-strength steel system prepared by the present invention is not limited to the above laser additive manufacturing technology, and the embodiments do not constitute a limitation on the protection scope of the present invention. Any equivalent replacement or change based on the technical solution and inventive concept of the present invention shall fall within the protection scope of the patent of the present invention.
Claims
1. A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, characterized in that: Its chemical composition by mass percentage is: C: 0.20~0.65%, Mn: 3.0~6.5%, Cr: 0.6~1.4%, Si: 0.6~2.8%, Al: 0.6~1.5%, and the balance is Fe.
2. A manganese-silicon-aluminum-chromium high-strength steel suitable for additive manufacturing, characterized in that: Its chemical composition by mass percentage is: C: 0.30~0.45%, Mn: 3.8~5.0%, Cr: 0.8~1.2%, Si: 0.9~1.6%, Al: 0.8~1.2%, and the balance is Fe.
3. A method for manufacturing manganese-silicon-aluminum-chromium high-strength steel based on laser additive manufacturing, characterized in that: The specific steps include: (1) According to the composition ratio of the manganese-silicon-aluminum-chromium high-strength steel as claimed in claim 1 or 2, high-strength steel powder with a particle size of 15 to 53 μm is prepared by vacuum melting, gas atomization and powder screening; (2) Using the high-strength steel powder obtained in step (1), a high-strength steel block is prepared by laser powder bed melting additive manufacturing technology.
4. The method according to claim 3, characterized in that High-strength steel blocks were prepared by laser powder bed fusion additive manufacturing technology, and the process parameters were set as follows: a laser with a spot diameter of 130 μm was selected, a scanning strategy of rotating the laser scanning direction by 67° per layer was adopted, the laser power was set to 180-260 W, the scanning speed was set to 600-1800 mm / s, the scanning interval was set to 70 μm, and the powder layer thickness was set to 30 μm.
5. The method according to claim 3, characterized in that The room temperature tensile strength, yield strength and elongation of the prepared manganese-silicon-aluminum-chromium high-strength steel are 1300~1650 MPa, 1050~1450 MPa and 8.0~24.0%, respectively.